BPI - Banco Português do Investimento : equity research - Simões, Inês Guedes de Andrade Costa (2013)
In the recent years, many valuation models have been developed, and the debate on how best to estimate a company’s value, which assumptions should be made and what are the most adequate approaches to apply is still ongoing. The purpose of this dissertation is to bring some clarity upon Equity Research, by combining a review of considerable academic literature with the valuation of Banco Português de Investimento. In the end, I will also do a comparison for both methodologies followed and results obtained by Caixa Banco de Investimento in their report published on the 12th December 2011.